Modelling Motivational Techniques with Teachers' Job satisfaction in Private Secondary Schools - Omotayo AWODIJI; Josiah Owolabi; Abbas Rizvi Riffat; Paul Kobina Effrim (International Journal of Theory and Application in Elementary and Secondary School Education, 2022)
Human needs have generally been accepted as one of the essential components of institutional success. Private schools have surpassed public schools in Nigeria at all levels in terms of numbers and performance outcomes, yet their teachers' job satisfaction has been an issue of concern. This study, therefore, modeled the perceived motivational techniques adopted and their relationship with teachers' job satisfaction. The non-experimental survey design was adopted. Two hundred and fifty participants were randomly selected from a population of 700. The researcher-designed questionnaires called motivational techniques, and teachers' job satisfaction scales were used for data collection. Factor analysis was carried out to estimate construct validity, while Cronbach Alpha was used to ascertain the instruments’ internal consistency (r=0.842 & r=0.958). Results showed that income, promotion, working conditions, and recognition influence private teachers' job satisfaction. Also, income significantly relates to job satisfaction. For practice, private school administrators should design policies using the model to promote teachers' satisfaction, thus facilitating the better performance of students and teachers.